Stream channel morphology and water flow in ice-free areas of Byers Peninsula, South Shetland Islands, Antarctica - Ortega-Becerril, José Antonio; Schmid, Thomas; Corella, Juan Pablo; Carcavilla, Luis; Calle, Mikel; López-Martínez, Jerónimo (Elsevier, 2026)
Fluvial stream channels in Antarctic ice-free areas provide valuable insights into deglaciation/neoglaciation, and the pace of morphogenetic processes shaping the landscape. The northern Antarctic Peninsula, particularly the South Shetland Islands, offers unique conditions for such studies due to extensive ice-free zones, glacial history, and rapidly changing environments. This research focuses on Byers Peninsula (BP), the largest ice-free area of the archipelago, characterized by a well-developed drainage system previously studied and mapped. This paper expands knowledge of channel development, water flow, and related morphologies, relevant for understanding other ice-free Antarctic regions. Morphometric analyses were conducted on 26 streams, alongside evaluation of channel equilibrium in three selected watersheds. Water flow was monitored for two years in two streams using data loggers, with complementary field data from a third. Seven morphotypes were distinguished within a theoretical watershed, including diffuse drainage, platform lakes, braided systems, canyons, cutting raised platforms, open braided channels, entrenched channels on raised beaches, lagoons and/or small fans. Results highlight significant variability in channel size and hydraulic properties across sub-basins. Southern BP streams reveal higher fluvial energy, while Western streams, draining larger basins with higher stream orders, display more advanced fluvial development and concentrate the main systems of the region. Basin orientation, glacier proximity, and topography emerged as key factors shaping channel dimensions, while glacial lake outburst floods strongly influenced morphology and sediment dynamics. The presence of paired morphometrically similar channels on North and South coasts supports a stepwise west–east retreat of Rotch Dome Glacier, marked by stagnation phases producing mature channels and rapid retreats yielding less developed systems.